Implementasi Pembelajaran Cooperative Learning Tipe Talking Stick (CLTTS) - Aziz Najimuddin (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2021)
The purpose of this study was to increase the activities and outcomes of learning English with the subject of Imperative Sentence. The research subjects were 25 students of class VIII.F SMP Negeri 1 Mandirancan. Data collection techniques using the method of observation, documentation and tests. The validity of this classroom action research is through triangulation. Data analysis using qualitative descriptive techniques. The increase in student activity shows that the acquisition in the initial study was only 32.00% or 8 students increased to 68.00% in the first cycle or as many as 17 students, and in the second cycle it was 92.00% or as many as 23 students were declared complete. The increase in student learning outcomes from the average in the initial study was only 64.80 to 75.60 in the first cycle, and in the second cycle to 85.60 and an increase in learning completeness from 5 students or 20.00% to 14 students or 56.00 % and 22 students or 88.00% in the second cycle.